Mechanical, Thermal Degradation, and Flammability Studies on Surface Modified Sisal Fiber Reinforced Recycled Polypropylene Composites. (13th December 2012) - Gupta, Arun Kumar; Biswal, Manoranjan; Mohanty, S.; Nayak, S. K.
Abstract : The effect of surface treated sisal fiber on the mechanical, thermal, flammability, and morphological properties of sisal fiber (SF) reinforced recycled polypropylene (RPP) composites was investigated. The surface of sisal fiber was modified with different chemical reagent such as silane, glycidyl methacrylate (GMA), and O-hydroxybenzene diazonium chloride (OBDC) to improve the compatibility with the matrix polymer. The experimental results revealed an improvement in the tensile strength to 11%, 20%, and 31.36% and impact strength to 78.72%, 77%, and 81% for silane, GMA, and OBDC treated sisal fiber reinforced recycled Polypropylene (RPP/SF) composites, respectively, as compared to RPP. The thermogravimetric analysis (TGA), differential scanning calorimeter (DSC), and heat deflection temperature (HDT) results revealed improved thermal stability as compared with RPP. The flammability behaviour of silane, GMA, and OBDC treated SF/RPP composites was studied by the horizontal burning rate by UL-94. The morphological analysis through scanning electron micrograph (SEM) supports improves surface interaction between fiber surface and polymer matrix.